EMPLOYABILITY STATUS OF ENGLISH LANGUAGE STUDIES GRADUATES IN A POLYTECHNIC STATE COLLEGE IN THE PHILIPPINES - Marlon S. Pontillas; Dan Fereth B. Fajardo (English Journal Literacy Utama, 2023)
This study examines the employability of graduates from the AB English Language Studies program at Camarines Sur Polytechnic Colleges (CSPC) in the Philippines, with a specific emphasis on the 2022 batch. This study examines the correlation between the educational background of graduates and their career outcomes, evaluates the program's influence on the academic and professional development of individuals, and assesses the pertinence of the curriculum. The study used a mixed-methods research methodology, incorporating both surveys and interviews, to thoroughly comprehend the graduates' experiences and perceptions. The results indicate a significant correlation between the AB English program and the employment outcomes of its alumni, since a majority of them reported securing jobs that are closely aligned with their educational background. Graduates also recognize the program's favorable impact on academic, communicative, and professional advancement. The curriculum is considered comprehensive and pertinent, with high levels of student satisfaction